Effect of Fire Flame (High Temperature) on the Behaviour of Axially loaded Reinforced SCC Short Columns (Journal of Engineering, 2012)
Experimental research was carried out to investigate the effect of fire flame (high temperature) on specimens of short columns manufactured using SCC (Self compacted concrete). To simulate the real practical fire disasters, the specimens were exposed to high temperature flame, using furnace manufactured for this purpose. The column specimens were cooled in two ways. In the first the specimens were left in the air and suddenly cooled using water, after that the specimens were loaded to study the effect of degree of temperature, steel reinforcement ratio and cooling rate, on the load carrying capacity of the reinforced concrete column specimens. The results will be compared with behaviour of columns without burning (control specimens). The results showed that, the ultimate load capacity of columns exposed to fire decreases with increasing the fire flame temperature. At burning temperature 300 Co , 500 Co and 700 Co , the average residual ultimate load capacity for gradually cooled specimens were 91%, 81% and 71% respectively. By increasing the ratio of longitudinal reinforcement 44% , the maximum improvement in the ultimate load capacity was 24% and 17% for the gradually and sudden cooling respectively at Co 500 . For the same longitudinal reinforcement ratio and fire burning temperature, the ultimate capacity for the sudden cooling specimens was less than that of gradually cooled specimens by about 10%.